2021
DOI: 10.3389/fonc.2021.697247
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Metabolomic and Network Pharmacology Study Revealing the Regulating Properties of Xihuang Pill That Improves Anlotinib Effects in Lung Cancer

Abstract: Lung cancer ranks as a leading cause of death. Although targeted therapies usually trigger profound initial patient responses, these effects are transient due to drug resistance and severe side effects. Xihuang Pill (XHW) is a popular Chinese medicine formula that might benefit cancer patients when used as a complementary therapy. However, its underlying mechanism when combined with anticancer drugs is not clearly understood. Here, we used an integrated strategy to reveal the regulatory properties of XHW in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Moreover, LA produces arachidonic acid (AA), which can produce prostaglandins (PGs) and leukotrienes (LTs) under the action of cyclooxygenase (COX). Studies have shown that increasing LA intake may decrease the risk of pneumonia [ 32 ]. Moreover, AA has activity against bacteria, fungi, and influenza viruses, whereas alveolar macrophages can release AA and other unsaturated fatty acids into alveolar fluid, thereby exerting their antibacterial impact and protecting the lungs from various microbial infections [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LA produces arachidonic acid (AA), which can produce prostaglandins (PGs) and leukotrienes (LTs) under the action of cyclooxygenase (COX). Studies have shown that increasing LA intake may decrease the risk of pneumonia [ 32 ]. Moreover, AA has activity against bacteria, fungi, and influenza viruses, whereas alveolar macrophages can release AA and other unsaturated fatty acids into alveolar fluid, thereby exerting their antibacterial impact and protecting the lungs from various microbial infections [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the experimental group showed better post-treatment levels (CD3 + CD4+, MD = 7.06, 95% CI: 3.56-10.57, P < .0001; CD3 + CD8+, MD = 5.49, 95% CI: 2.30-8.69, P = .0008; CD3 − CD56+, MD = 4.99, 95% CI: 2.07-7.91, P = .0008), and there was no significant heterogeneity (CD3 + CD4+, χ 2 = 0.16, P = .69, I 2 = 0%; CD3 + CD8+, χ 2 = 0.74, P = .39, I 2 = 0%; CD3 − CD56+, χ 2 = 0.16, P = .69, I 2 = 0%) (Figs. [20][21][22]. Moreover, patients treated with Xihuang Pills/Capsules in combination with Western medicine had higher immunoglobulin M levels (MD = 0.52, 95% CI: 0.11-0.93, P = .01, 2 studies, 158 patients).…”
Section: 44mentioning
confidence: 99%
“…Today, Xihuang Pills/Capsules find extensive application in clinical research as adjuvant therapy for various malignant tumors, including breast cancer, colorectal cancer, ovarian cancer, lung cancer, liver cancer, and lymphoma. [17][18][19][20][21][22] However, there is currently a lack of evidence-based medical studies on uterine cervical neoplasms. Consequently, to assess the clinical safety of Xihuang Pills/ Capsules when combined with other therapies for treating cervical neoplasms, this study conducted a meta-analysis of randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
“…9 These diseases include but are not limited to coronary heart disease, 10 type 2 diabetes mellitus, 11 metabolic diseases, 12 traumatic brain injury, 13 Alzheimer's disease 14 and lung cancer. [15][16][17] Network pharmacology is also increasingly applied in the research of traditional Chinese medicine. 18 Abundant information including bioactive compounds, targets, and the interactions between these can be obtained by constructing a network pharmacology model.…”
Section: Introductionmentioning
confidence: 99%